2021
DOI: 10.2147/oarrr.s314421
|View full text |Cite
|
Sign up to set email alerts
|

ANCA-Associated Vasculitis Clinical Presentation and Clinical Predictors of Relapse in Saudi Arabia

Abstract: Background: Anti-neutrophil cytoplasm antibodies-associated vasculitis (AAV) is a rare autoimmune condition with high-relapsing rate and incidence of complications, resulting in increased morbidity and mortality. Characters of patients with anti-neutrophil cytoplasm antibodies-associated vasculitis in Saudi Arabia require further exploration. Objective: To evaluate the clinical profile, relapse rate and disease-related complications among patients with AAV at a tertiary hospital in Saudi Arabia. To estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Other studies have reported similar results. 29,30 Pulmonary manifestations were common in our cohort of patients with GPA and MPA, similar to previous studies. 29,30 Due to the high percentage of patients with lower lung involvement (77.8%), various complications were identified, with infection (10%) being the most common.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies have reported similar results. 29,30 Pulmonary manifestations were common in our cohort of patients with GPA and MPA, similar to previous studies. 29,30 Due to the high percentage of patients with lower lung involvement (77.8%), various complications were identified, with infection (10%) being the most common.…”
Section: Discussionsupporting
confidence: 90%
“…Pulmonary manifestations were common in our cohort of patients with GPA and MPA, similar to previous studies. 29,30 Due to the high percentage of patients with lower lung involvement (77.8%), various complications were identified, with infection (10%) being the most common. While pulmonary manifestations were slightly more common in our patients with GPA, more serious respiratory conditions were present in our patients with MPA.…”
Section: Discussionmentioning
confidence: 99%
“…Antineutrophil cytoplasmic antibody mediated vasculitis includes several subtypes of diseases including Wegner's granulomatosis where the C-ANCA or anti-PR3 is positive in around 90% of the cases. The other one is the MPA or microscopic polyangiitis (Churg -Strauss disease) in which the myeloperoxidase (MPO) antibody is positive with a positive perinuclear antibody P-ANCA positive pattern [6].…”
Section: Discussionmentioning
confidence: 99%
“…3 These disorders tend to occur equally in both genders, with a peak age between 65 and 74 years at diagnosis. 4 Individuals diagnosed with AAV can present with severe clinical symptoms that may threaten their lives, for example, alveolar hemorrhage and rapidly progressive glomerulonephritis, while other patients may complain of a less severe clinical picture involving any part of the upper respiratory tract. 5 Two fluorescence patterns of ANCAs distinguished by indirect immunofluorescence (IIF) have been associated with AAV: the cytoplasmic staining pattern (C-ANCA) and perinuclear staining pattern (P-ANCA).…”
mentioning
confidence: 99%
“…14 The characteristics of patients with AAV in Saudi Arabia require further exploration. 4 Numerous studies have been conducted on AAV in Saudi Arabia, many of which have explored the manifestations of these disorders. 15 Research into these disorders is not common; as such, we sought to understand the most common type and clinical manifestations of AAV and to gain additional background knowledge to publish more studies in this field.…”
mentioning
confidence: 99%